2007
DOI: 10.1152/ajpgi.00096.2007
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor (TLR) 2 induced through TLR4 signaling initiated byHelicobacter pyloricooperatively amplifies iNOS induction in gastric epithelial cells

Abstract: Cell-surface Toll-like receptors (TLRs) initiate innate immune responses, such as inducible nitric oxide synthase (iNOS) induction, to microorganisms' surface pathogens. TLR2 and TLR4 play important roles in gastric mucosa infected with Helicobacter pylori (H. pylori), which contains lipopolysaccharide (LPS) as a pathogen. The present study investigates their physiological roles in the innate immune response of gastric epithelial cells to H. pylori-LPS. Changes in the expression of iNOS, TLR2, and TLR4, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 35 publications
(56 reference statements)
4
66
1
4
Order By: Relevance
“…Infection with H. pylori enhances gastric epithelial expression of TLR2 in vitro and is associated with strongly upregulated apical epithelial expression of TLR2 in human gastric biopsy specimens (43). H. pylori lipopolysaccharide has been shown to activate epithelial TLR2 to stimulate cell proliferation and the production of inflammatory chemokines via induction of mitogen-activated protein kinase (MAPK) (52) and NF-B (36) signaling, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection with H. pylori enhances gastric epithelial expression of TLR2 in vitro and is associated with strongly upregulated apical epithelial expression of TLR2 in human gastric biopsy specimens (43). H. pylori lipopolysaccharide has been shown to activate epithelial TLR2 to stimulate cell proliferation and the production of inflammatory chemokines via induction of mitogen-activated protein kinase (MAPK) (52) and NF-B (36) signaling, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In airway epithelia, toll-like receptor 2 (TLR2)-induced calcium fluxes have been shown to mediate bacterially induced calpain activation, leading to cleavage of E-cadherin (8). H. pylori lipopolysaccharide is a TLR2 agonist, and TLR2 expression is strongly upregulated on the apical surface of the gastric mucosa of H. pylori-infected patients and H. pylori-challenged cultured gastric epithelial cells (36,43,52). In light of these findings, we hypothesized that calpain may mediate H. pylori-induced AJ defects and aimed to assess the roles of TLR2 and calpain in H. pyloriinduced AJ disruption using human samples and an in vitro gastric epithelial model.…”
mentioning
confidence: 99%
“…Some studies have provided strong evidence that TLR4 is expressed by gastric epithelial cells and the LPS of H. pylori is involved in the signaling pathways leading to the production of proinfl ammatory cytokines [20][21][22]; however, some other studies have shown contradictory results; e.g., the study by Smith et al [11] revealed that H. pylori LPS is a TLR2 ligand and not a TLR4 ligand. Later, it was also shown that TLR4 signaling initiated by H. pylori LPS induced TLR2 expression in gastric epithelial cells [23]. For the association between polymorphisms in the TLR genes and the risk of gastric cancer, associations between polymorphisms in the TLR4 gene and the risk of gastric cancer are well documented, although there exists only one report regarding the association between polymorphisms in the TLR2 gene and the risk of gastric cancer [12].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in addition to monocyte differentiation antigen (CD14) and myeloid differentiation protein (MD-2), TLR4 can interact with LPS, and this interaction induces signal transduction pathways that activate NF-κB and cause the expression of several cytokines, including TNF-α, IL-1β, IL-6 and IL-12 (29). Additionally, TLR2 induces cell proliferation and TLR4 activation expression via the MEK1/2-ERK/2 pathway (13,30).…”
Section: Discussionmentioning
confidence: 99%